2018
DOI: 10.21276/ap.2018.7.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Original article Antibacterial and anticandidal effects of the leaf extracts of Perseaamericana Mill.

Abstract: In this study, the antibacterial and anticandidal effects of the leaf extracts of Persea americana Mill. were examined against some pathogenic bacteria and some Candida species. Plant leaves were reduced to powder with liquid nitrogen. n-propanol, methanol, acetone, n-hexane, ethyl acetate, ethanol and boiling water as solvents were used for extraction. The agar well diffusion method is u sed for the a ntimicrobia l activities of extra cts. Test microorga nisms were 1 8 bacteria and 4 yeasts. Also, different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The avocado seeds have been traditionally used as remedies to treat asthma, inflammation, and mainly diarrhea and infectious diseases [ 16 , 17 ]. These effects have been mainly associated to the presence of secondary metabolites such as polyphenols [ 18 ]. In a previous study, we demonstrated that ethanol extracts from the seeds of P. americana growing in the Cuban eastern region showed a phytochemical composition rich in polyphenols such as catechins and neolignans derivatives as well as some fatty acids/alcohols as main [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The avocado seeds have been traditionally used as remedies to treat asthma, inflammation, and mainly diarrhea and infectious diseases [ 16 , 17 ]. These effects have been mainly associated to the presence of secondary metabolites such as polyphenols [ 18 ]. In a previous study, we demonstrated that ethanol extracts from the seeds of P. americana growing in the Cuban eastern region showed a phytochemical composition rich in polyphenols such as catechins and neolignans derivatives as well as some fatty acids/alcohols as main [ 19 ].…”
Section: Introductionmentioning
confidence: 99%